Students as change agents for campus sustainability in Malaysian universities. Issue 1 (4th January 2021) - Mohamad, Zeeda Fatimah; Mamat, Mohd Zufri; Muhamad Noor, Muhamad Faisal
Abstract : Purpose: The notion of students as change agents have widely been used in the campus sustainability literature, but very little has been done to unpack what it really means in practice. This paper aims to critically investigate university students' perspectives on their role as a change agent for campus sustainability in the context of Malaysian universities. Design/methodology/approach: In-depth interviews were carried out with 21 students that have been categorized as change agents through selection criteria at three leading universities in the area of campus sustainability in Malaysia. The data collected from the interviews were analysed through content-based and thematic analysis. Findings: Findings demonstrate that students are the backbone behind the implementation of campus sustainability activities. They play the multi-faceted role of leaders, supporters and ambassadors in initiating and driving campus sustainability. The results further suggest that support and freedom to act are the empowering factors that have driven these change agents in carrying out their initiatives. However, without a position, the students' voices are not significant. Originality/value: This study provides deeper evidence-based insights on the notion of students as change agents and how it can be operationalized in the context of campus sustainability.